2014
DOI: 10.1155/2014/723238
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in Healthy South Indian Males and the Influence of Life Style Factors and Vitamin D Status on Bone Mineral Density

Abstract: Objective. To study the prevalence of osteoporosis and vitamin D deficiency in healthy men and to explore the influence of various life style factors on bone mineral density (BMD) and also to look at number of subjects warranting treatment. Methods. Ambulatory south Indian men aged above 50 were recruited by cluster random sampling. The physical activity, risk factors in the FRAX tool, BMD, vitamin D, and PTH were assessed. The number of people needing treatment was calculated, which included subjects with ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 25 publications
6
47
1
Order By: Relevance
“…9 Also Shetty et al reported slightly lesser values of osteoporosis (20%) but slightly higher values of osteopenia (58%) in south Indian men aged above 50 years when compared to this study. 18 In this study, the bone mineral density decreased as the age advances among men, especially after 40 years of age which is also identical to the findings by Agarwal and Sharma who found that BMD decreases as age advances in a study carried out among 200 healthy men aged above 50 years. 19 The current guidelines suggest screening for osteoporosis in asymptomatic Caucasian men above 70 years of age and in men in the age group 50-69 with additional risk factors but there is a paucity of recommendations for Indian men.…”
Section: Discussionsupporting
confidence: 91%
“…9 Also Shetty et al reported slightly lesser values of osteoporosis (20%) but slightly higher values of osteopenia (58%) in south Indian men aged above 50 years when compared to this study. 18 In this study, the bone mineral density decreased as the age advances among men, especially after 40 years of age which is also identical to the findings by Agarwal and Sharma who found that BMD decreases as age advances in a study carried out among 200 healthy men aged above 50 years. 19 The current guidelines suggest screening for osteoporosis in asymptomatic Caucasian men above 70 years of age and in men in the age group 50-69 with additional risk factors but there is a paucity of recommendations for Indian men.…”
Section: Discussionsupporting
confidence: 91%
“…17 Shetty et al reported slightly lesser values of osteoporosis (20%) and slightly higher values of osteopenia (58%) in south Indian men aged above 50 years. 18 Whereas in our study out of 250 male participants, 5 (2%) and 51 (20.4%) participants were found to satisfy the criteria of ≥20% major osteoporotic risk and ≥3% hip fracture risk respectively.…”
Section: Discussioncontrasting
confidence: 50%
“…These observations highlight that though indirect sun exposure can prevent VDD, for vitamin D sufficiency outdoors workers need to have direct sun exposure. The observation of near normal serum 25(OH)D of 50.0 nmol/L is common in southern India that receives more sunlight than north India . Present study indicates that it is possible to have normal serum 25(OH)D naturally in outdoor workers of northern Indian region.…”
Section: Discussionmentioning
confidence: 81%